2021
DOI: 10.7759/cureus.16544
|View full text |Cite
|
Sign up to set email alerts
|

The Association of the Prolonged Use of Personal Protective Equipment and Face Mask During COVID-19 Pandemic With Various Dermatologic Disease Manifestations: A Systematic Review

Abstract: COVID-19 is a novel coronavirus that represents a great global health concern. It is transmitted between individuals through respiratory particles, and as there is no established effective treatment currently for the virus, it is necessary to use protective strategies such as face masks. Healthcare providers and individuals serving outdoors are required to work for long durations wearing personal protective equipment (PPE). Wearing such protective equipment may have short-or long-term effects on the skin healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…In addition, no significant correlation was found among those who used face masks for 8 hours or more, but many participants reported that their symptoms occurred when they used masks for more than 17 hours. This is consistent with a systematic review published by Barnawi et al,2 in which the occurrence of dermatological complications from wearing personal protective equipment (PPE) was reported to be more apparent among individuals wearing PPE for more than 4 hours a day. Many participants described symptoms that appeared when they use masks for 5 days a week.…”
supporting
confidence: 92%
“…In addition, no significant correlation was found among those who used face masks for 8 hours or more, but many participants reported that their symptoms occurred when they used masks for more than 17 hours. This is consistent with a systematic review published by Barnawi et al,2 in which the occurrence of dermatological complications from wearing personal protective equipment (PPE) was reported to be more apparent among individuals wearing PPE for more than 4 hours a day. Many participants described symptoms that appeared when they use masks for 5 days a week.…”
supporting
confidence: 92%
“…Thus, seeing greater odds of HCWs wearing respirators experiencing pressure sores, facial itching or irritation, headaches and shortness of breath or respiratory distress is unsurprising. These effects might also be exacerbated the longer the mask is worn for ( 19 , 47 ). Although these findings are supported by similar recently published literature ( 48 ), the small number of studies, wide confidence intervals, small sample sizes and the substantial potential for confounding (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, mandating mask and respirator use might not lead to use, suggesting that barriers to use are important considerations when mandating specific PPE ( 16 ). During the pandemic, HCWs have needed to wear PPE for several hours and days in a row, rendering them susceptible to adverse events (AEs) associated with prolonged contact between mask material and the skin ( 17 , 18 , 19 ), such as injury and absenteeism ( 20 ), prompting measures to be taken to protect the skin of HCWs wearing PPE ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the dental field, wearing a custom-fit N95 respirator with a patent seal all around offers superior protection against infectious bioaerosols [18]. However, prolonged wearing of RPE and other additional PPE compresses the cheeks, forehead, bridge of the nose, and ears, which can be the main reason for head and face pressure and skin damage [22][23][24][25]. The lack of proper training in PPE use and successive wearing of them further complicates these issues [21].…”
Section: Surgical Facemasks Versus N95 Respiratorsmentioning
confidence: 99%